Validation of bioanalytical method for quantification of Vitamin K2 (MK-4) in human plasma by high-performance liquid chromatography-ultraviolet - Norisca Aliza Putriana; Taofik Rusdiana; Nurhanifah Puspitadewi; Driyanti Rahayu; Febrina Amelia Saputri (Wolters Kluwer Medknow Publications, 2023)
Vitamin K can reduce warfarin's anticoagulant action, causing a variance in response among individuals taking warfarin. Vitamin K comes in two forms, namely Vitamin K1 (phylloquinone) and K2 (menaquinones). Menaquinone-4 (MK-4) is a kind of Vitamin K2 found in meat and dairy products. Analysis of MK-4 levels in human plasma is very useful for patients who receive warfarin therapy. High-performance liquid chromatography (HPLC) can be used for warfarin's bioanalysis, and it must be validated. The purpose of this study was to validate the bioanalytical method for quantification of Vitamin K2 (MK-4) in human plasma according to the 2019 European Medicines Agency (EMA) guideline. Vitamin K2 (MK-4) was extracted using acetonitrile. HPLC with an ultraviolet detector at 245 nm, using a T3 column set at 30°C and an isocratic mobile phase containing methanol: phosphate buffer (95:5) at pH 3, a flow rate of 1 mL/min was used in this study. The warfarin concentration of 0.5-3 μg/mL was used. About 5.50%-17.42% and 6.18%-8.74%, respectively, were the average ranges of percentage coefficient of variation and percentage difference. There was no response at the analyte's retention time in the six blank plasmas and at the analyte's retention time in the blank after the injection of upper limit of quantification, indicates that the procedure was very selective and did not result in any carryover. This bioanalytical method fulfills the parameters of selectivity, accuracy, precision, and carryover based on the 2019 EMA guidelines.